Noise in the mining operation The case Yanacocha west - Plasencia Sánchez, Edson (2009)
Although almost all human activities produce noise, these may keep in a such level that can’t produce an adverse impact on the people health’s and be according to its environment, so, the countries rule the noise production and adopt environmental standards for noise. In this paper, the document titled : “Modificación al Plan de Monitoreo Ambiental Suplementario de Yanacocha Oeste” is considered and analyzed technically like an example of the environmental transcendence for these kind of documents when are presented to the sector authority.